UPAYA PENINGKATAN SUMBER DAYA MANUSIA DI SMP AL HUDA JATI AGUNG LAMPUNG SELATAN DALAM PERSPEKTIF AL QUR’AN DAN AL HADIST - AHMAD MUNIR (UNISAN JURNAL, 2024)
In this research, the human resources section of Al Huda Jatiagung Middle School, South Lampung, will be studied and its efforts will be described. Qualitative descriptive methods were used in this research. a place where scientists conduct field research directly. This research uses primary and secondary data sources as data. Using observation, interview, and documentation methods carried out at Al Huda Middle School, Jati Agung, South Lampung, three people provided information for this research: the head of the Sekolah, the deputy head of curriculum, and a subject teacher. . uses an interactive analysis model for data analysis consisting of data reduction, data presentation for inference, and data verification. uses triangulation techniques, member verification, long-term observation, peer review, collaborative research participation modalities, researcher bias, negative case analysis, concise description, and auditing to verify data quality. There are three conclusions that can be drawn from the findings of this research: 1. Although Al Huda Middle School in Jatiagung, South Lampung has quite good human resources (HR), there is still room for improvement. This is because there is still a lack of discipline between teachers and staff, and many teachers continue to teach courses that are not relevant to their field of expertise at the Sekolah